On the impact of current generation commercial gallium nitride power transistors on power converter loss. Issue 22 (1st October 2017) - Petersen, A.; Stone, D.A.; Foster, M.P.
Abstract : The enormous potential benefits of gallium nitride based power switching devices, only commercially available very recently, in terms of power switching device loss are highlighted. This is first demonstrated through a simulated prediction of loss in multilevel converters, followed by experimental validation. While the simulations focus on losses in multilevel converters, the observations made are relevant in a broad range of applications.